2009
DOI: 10.1016/s1726-4901(09)70038-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Central Corneal Thickness, Refractive Error, Corneal Curvature, Anterior Chamber Depth and Axial Length

Abstract: CCT was not associated with refractive error, corneal curvature, anterior chamber depth and axial length. CCT is an independent factor unrelated to other ocular parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
69
5
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 24 publications
24
69
5
1
Order By: Relevance
“…The average CCT of this study was smaller than the 563.0 38.0 and 562.8 31.3µm reported for Caucasians by Aghaian et al (2004) and Semes et al (2006). This value was close to that of the Taiwanese Chinese (554.0 29.0µm) (Chen et al, 2009).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The average CCT of this study was smaller than the 563.0 38.0 and 562.8 31.3µm reported for Caucasians by Aghaian et al (2004) and Semes et al (2006). This value was close to that of the Taiwanese Chinese (554.0 29.0µm) (Chen et al, 2009).…”
Section: Discussionsupporting
confidence: 57%
“…The potential for central corneal thickness to significantly impact on the intraocular pressure, including diagnosis and management options of glaucoma, has aroused great interest in its distribution in different populations (Dueker et al, 2007) and races (Hahn et al, 2003;Shimmyo et al, 2003;Aghaian et al, 2004;Kohlhaas et al, 2006;Mercieca et al, 2007;Iyamu and Ituah, 2008;Chen et al, 2009). Several factors affect the central corneal thickness including race, ethnicity, age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Central corneal thickness is not associated with age, gender, occupation, refractive error, corneal curvature, anterior chamber depth, or axial length [28][29][30]. Hepsen and co-authors found thicker central cornea in patients with PEX than in the control group using the Pentacam imaging system [31].…”
Section: Resultsmentioning
confidence: 98%
“…A great number of reports have shown a negative relationship between AL and myopia. In other words, the longer the AL, the severer the myopia [41,42]. Olsen et al [35] found that when considering the contribution of AL, lens power and corneal power together, using multiple linear regression analyses, it can explain up to 96% of the variation of refraction in populations.…”
Section: Axial Lengthmentioning
confidence: 99%